Purification and properties of a fifth major viral gag protein from avian sarcoma and leukemia viruses. - Pepinsky, R B (1983)
We have developed procedures for the purification of a 6,000-dalton protein from avian myeloblastosis virus. This protein is a major component of avian myeloblastosis virus, accounting for over 7% of total protein, and thus is equimolar with the other internal structural proteins in virions. As described in the accompanying paper (Hunter et al., J. Virol. 45:885-888, 1983), the results of N-terminal amino acid sequence analysis identify the protein as a product of the gag gene. We suggest denoting this protein as p10, according to nomenclature that is already in use for a previously identified but poorly defined low-molecular-weight protein or proteins of avian sarcoma and leukemia viruses. In virions p10 appears to be located between the core and the membrane. Several of its properties may explain why p10 has not been characterized previously. Among these are its abnormal amino acid composition, its solubility under conditions where most proteins are fixed into sodium dodecyl sulfate-polyacrylamide gels, and the variability in its electrophoretic migration in different avian sarcoma viruses.